Konstruksi dan Analisis Psikometrik Skala Motivasi Belajar Matematika Siswa SMP: Penelitian - Yuli Bangun Nursanti; Hendrisa Rizqie Romandoni; Dzalfadina Tri Hastiti Cahyaningrum; Lutvia Gravika Aspira; Kania Fauziati Naila; Ririn Mardiyanti; Indra Jati Mukminan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The absence of a standardized instrument contextualized for Indonesian students was a primary problem motivating this research, which aimed to develop and validate the Mathematics Learning Motivation Scale (MLMS) for junior high school students. This study employed a systematic instrument development process. The scale was constructed based on a synthesis of motivation theories, specifically operationalizing four key aspects: choice of tasks, effort, persistence, and self-confidence. These aspects were formulated into 30 Likert-scale items. The validation method included content validity, which was established through expert judgment from two education experts, and construct validity. The subjects for the validation trial were 31 eighth-grade students from a junior high school in Boyolali. The primary instrument used was the 30-item MLMS questionnaire itself. Data analysis was performed using SPSS version 22. The results from the Pearson product-moment correlation showed that all 30 items were valid, with each item's rcalculated score exceeding the rtable value of 0.355 at a 5% significance level. Furthermore, the reliability analysis reported a Cronbach's Alpha coefficient of 0.917, demonstrating very high internal consistency. It was concluded that the developed MLMS is a valid and highly reliable instrument, suitable for objectively measuring mathematics learning motivation in this specific student context.